Phosphorus–nitrogen compounds. Part 42. The comparative syntheses of 2-cis-4-ansa(N/O) and spiro(N/O) cyclotetraphosphazene derivatives: spectroscopic and crystallographic characterization, antituberculosis and cytotoxic activity studies. (26th April 2019) - Binici, Arzu; Okumuş, Aytuğ; Elmas, Gamze; Kılıç, Zeynel; Ramazanoğlu, Nagehan; Açık, Leyla; Şimşek, Hülya; Çağdaş Tunalı, Beste; Türk, Mustafa; Güzel, Remziye; Hökelek, Tuncer
Abstract : Syntheses, structural properties and biological activities of ferrocenyl ansa- and spiro-cyclotetraphosphazenes were investigated. Abstract : The reaction of N4 P4 Cl8 (1 ) with one equimolar amount of the sodium salt of an N/O donor-type bidentate ligand (2 ) afforded two kinds of derivatives, namely, mono-ferrocenyl-2- cis -4-dichloro-ansa- (2, 4-ansa;3 ) and mono-ferrocenyl-spiro- (spiro;4 ) hexachlorocyclotetraphosphazenes. The reaction yield (35%) of4 was significantly larger than that of3 (14%). The 2, 4-ansa compound (3 ) was reacted with excess secondary amines to produce 2- cis -4-dichloro-ansa-cyclotetraphosphazenes (3a–3d ). On the other hand, the spiro compound (4 ) gave fully substituted mono-ferrocenyl-spiro-cyclotetraphosphazenes (4a–4d ) with excess monoamines as well. The tetrameric phosphazene derivatives were characterized by ESI-MS and/or HRMS, FTIR, HSQC, HMBC, 1 H, 13 C, and 31 P NMR spectroscopy and X-ray crystallography (for4 ). It is observed that the 2, 4-ansa and spiro-cyclotetraphosphazenes have different thermal stabilities. Additionally, the CVs of the new mono-ferrocenyl pendant-armed cyclotetraphosphazenes revealed electrochemically reversible one-electron oxidation of the Fe-redox centre. The 2, 4-ansa phosphazenes (3 and3a–3d ) have two different stereogenic P centers indicating that they are expected to be in racemic mixtures ( RR ′/ SS ′). The chiralities of3a and3c were investigated by chiral HPLC. The manuscript also deals with the antimicrobial activities against G(+)/G(−) bacteria and fungi, the interactions with plasmid DNA, the in vitro cytotoxic activities against L929 fibroblast and MCF7 breast cells, and the antituberculosis activities against Mycobacterium tuberculosis H37Rv of the cyclotetraphosphazenes.